Α-Galactosides present in lupin flour affect several metabolic parameters in Wistar rats. Issue 12 (18th November 2016) - Palacio, María I.; Weisstaub, Adriana R.; Zuleta, Ángela; Etcheverría, Analía I.; Manrique, Guillermo D.
Abstract : The aim of this study is to evaluate the influence of α-galactosides present in a lupin diet on metabolic parameters in growing Wistar rats. Abstract : The aim of this study is to evaluate the influence of α-galactosides present in a lupin diet on metabolic parameters in growing Wistar rats. Lupin ( Lupinus albus ) is a rich source of non-digestible carbohydrates called α-galactosides whose beneficial health effects have been widely reported. For our investigation, twenty male Wistar rats were fed with two different diets: control (C) and lupin flour (L) for a 60-day period. The fermentation of these α-galactosides was monitored by measuring the following indicators: changes in the dynamic lactobacilli and enterobacteriaceae population, cecal content pH, generation of short chain fatty acids (SCFA), Ca and P absorption, and serum lipid (triglycerides and cholesterol) contents. The body weight was lower in the L diet than that in the control with significant differences ( p < 0.05). The microbial analyses showed an increase of total lactobacilli counts and a decrease of enterobacteriaceae counts in the L diet when compared to the control, with significant differences ( p < 0.05). The fermentations of α-galactosides were also confirmed by decrease in pH levels and the formation of relevant SCFA in the cecal content. The total content of SCFA (μmol per g) at the end of the assay period reached values of 13.58 and 3.64 for L and C rats, respectively. This significant increase of total SCFA in the L diet is responsible for a low pH of the cecal content that in turn prevents the growth and development of potentially pathogenic bacteria ( p < 0.05). Regarding lipids, serum triglycerides and cholesterol levels were significantly reduced in the case of animals fed with lupin flour with respect to C animals ( p < 0.05). Finally, the L rats showed higher values of an apparent Ca absorption percentage and bone volume percentage with respect to the C animals ( p < 0.05). All these results confirm that lupin flour which contains α-galactosides could possibly be considered as a functional ingredient with health promoting properties.